The Viscous Slime, Stickiness, Fondling, Mixtures - Mason, Freddie (punctum books, 2020)
Slime, goo, gunge, gloop, gels, sols, globules, jellies, emulsions, greases, soaps, syrups, glues, lubricants, liquid crystals, moulds, plasmas, and protoplasms - the viscous is not one thing, but rather a quality of resistance and flow, of stickiness and slipperiness. It is a state of matter that oozes into the gaps of our everyday existence, across age groups, between cultures and disciplines.Since the large-scale extraction of petroleum in the 19th century the viscous has witnessed a proliferation in the variety of its forms. Mechanized industry required lubricants and oil distillation produced waste products that were refined to form Vaseline. From this age, new viscous forms and technologies emerged, products from plastic (and plastic explosives) to cosmetics, glycerine, asphalt, sexual lubrication, hydro- and aero- gels, even anti-climb paint.Based on unique and wide-ranging research, The Viscous is the first major investigation of viscous encounter and possibility over the course of the last century, not simply as a material state, but also an imaginative event. We enter into a story of matter at its most wayward, deviant, hesitant, and resistant.From asphalt lakes to industrial molasses tanks, from liquid crystals squirming in our screens to milk fetishes, The Viscous discloses gooeyness as a peculiarly modern phase of matter. "Everything oozes," as Beckett's Estragon famously proclaims in Waiting for Godot. Viscous dynamics are exposed as not only hugely various in a post industrial age, but particularly useful ways of thinking, feeling, writing, and making in a time of ecological anxiety.